2022
DOI: 10.1002/hbm.25774
|View full text |Cite
|
Sign up to set email alerts
|

Tracer‐specific reference tissues selection improves detection of 18F‐FDG, 18F‐florbetapir, and 18F‐flortaucipir PET SUVR changes in Alzheimer's disease

Abstract: This study sought to identify a reference tissue-based quantification approach for improving the statistical power in detecting changes in brain glucose metabolism, amyloid, and tau deposition in Alzheimer's disease studies. A total of 794, 906, and 903 scans were included for 18 F-FDG, 18 F-florbetapir, and 18 F-flortaucipir, respectively. Positron emission tomography (PET) and T1-weighted images of participants were collected from the Alzheimer's disease Neuroimaging Initiative database, followed by partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…For instance, Li et al conducted a study on neurodegenerative diseases and found that the calculated SUVR was more effective in distinguishing between cognitively normal and cognitively impaired Alzheimer's patients when using the pons as the reference region compared to cerebellum gray matter and centrum semiovale [50]. In our study, the pons demonstrated superior performance in differentiating tumors from myelitis, both for SUVRmean and SUVRmax values, corresponding to its stable uptake characteristics.…”
Section: Discussionmentioning
confidence: 50%
“…For instance, Li et al conducted a study on neurodegenerative diseases and found that the calculated SUVR was more effective in distinguishing between cognitively normal and cognitively impaired Alzheimer's patients when using the pons as the reference region compared to cerebellum gray matter and centrum semiovale [50]. In our study, the pons demonstrated superior performance in differentiating tumors from myelitis, both for SUVRmean and SUVRmax values, corresponding to its stable uptake characteristics.…”
Section: Discussionmentioning
confidence: 50%
“…Subsequently, PET and CBF images were also normalized to the MNI space with the same transformation matrix. Moreover, 18 F‐FDG PET images were converted to standardized uptake value ratio (SUVR) maps, referring to the pons 24,25 …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, 18 F‐FDG PET images were converted to standardized uptake value ratio (SUVR) maps, referring to the pons. 24 , 25 …”
Section: Methodsmentioning
confidence: 99%
“…VOIs were manually drawn within descending aorta, duodenum, pancreas, and stomach using PMOD 4.3 software (PMOD Technologies Ltd.), where the descending aorta was selected to reflect the blood radiotracer concentration. To extract the TACs from the brain regions, all PET images were first processed by head motion correction and spatial normalization, both using Statistical Parametric Mapping software (SPM12, Wellcome Department of Imaging Neuroscience) in the MATLAB (2019b, The MathWorks Inc.) environment, followed by the co-registration of the PET images to the standard Montreal Neurologic Institute (MNI) space based on an MRI template 25 . Caudate, putamen, pallidum, and substantial nigra, which are the major brain regions associated with PD, were selected for the analysis.…”
Section: Dynamic Pet Image Processingmentioning
confidence: 99%